CALCULATION OF PRODUCTION COSTS USING JOB ORDER COSTING METHOD TO IMPROVE PROFIT ACCURACY AT LIDYA FURNITURE - Eny Widayawati (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2022)
This study aims to compare production costs at Lidya Furniture SMEs by calculating the principle of production costs using the Order Cost Method. Data was collected through observation, interviews, and documentation. Furthermore, the data were analyzed using qualitative methods. While the calculation method used in this study is the job order costing method or the cost of goods ordered. Based on the results of the analysis, the difference in the calculation of the cost of production is due to Lidya Furniture not identifying and detailing the elements of the cost of production, so that the cost of production calculated by Lidya Furniture is lower than using the job order costing method. We recommend that Lidya Furniture should correct the calculation of the cost of production according to the Order Cost Method, namely costing by calculating and identifying raw material costs, direct labor costs, and overhead costs so that the selling price determined can be accurate so as to increase profits.